تصميم وإنشاء تطبيق ويب للخدمات الحرفية والعمل عن بعد: منصة تجع بين الحرفيين والعملاء - عبد الرحمان حنه – عبد العالي دوح – معمر صالحي (university of eloued جامعة الوادي, 2024)
ا على الرغم من التطور التكنولوجي واستخدام الإنترنت في شتى مجالات الحياة، بما في ذلك الأعمال الرقمية والشركات التي تعمل عبر وسائل التواصل الاجتماعي أو المنصات الإلكترونية، لا تزال هناك حاجة لمنصة تجمع بين العملاء والحرفيين في مجالات متعددة مثل الطلاء والبناء والكهرباء وغيرها. وبالتالي العثور على الحرفي المناسب في الوقت المناسب يعد تحديا كبيرًا وعملاً شاقا لكل من العملاء والحرفيين. يهدف هذا المشروع إلى تطوير منصة إلكترونية موثوقة تُدعى "حرفة"، لتسهيل الوصول إلى حرفيين ماهرين في مختلف المجالات، مما يوفر الوقت والجهد للعملاء ويعزز فرص العمل للحرفيين. تتميز المنصة بواجهات سهلة الاستخدام تعرض مهارات وخبرات الحرفيين، بالإضافة إلى نظام تواصل مباشر بين العملاء والحرفيين. علاوة على ذلك، تحتوي المنصة على نظام تقييم يتيح للمستخدمين تقييم أداء الحرفيين، مما يساهم في تعزيز جودة الخدمات المقدمة وزيادة موثوقيتها. Despite technological advancements and the widespread use of the internet in various aspects of life, including digital businesses and companies operating through social media or electronic platforms, there is still a need for a platform that brings together customers and craftsmen in multiple fields such as painting, construction, electrical work, and others. Thus, finding the right craftsman at the right time remains a significant challenge and effort for both customers and craftsmen. This study aims to develop a reliable electronic platform called <Hirfa» to facilitate access to skilled craftsmen in various fields, saving time and effort for customers and enhancing job opportunities for craftsmen. The platform features user-friendly interfaces showcasing the skills and experiences of craftsmen, along with a direct communication system between customers and craftsmen. Additionally, the platform includes a rating system that allows users to evaluate the performance of craftsmen, contributing to the enhancement of the quality and reliability of the services provided.
مدكرة ليسانس اعلام الي
Keywords: حرفيين، بناء ، صباغة، كهربائي، منصة إلكترونية، موقع ويب، نظام تقييم.; craftsmen; construction; painting; electrical work; electronic platform; website; rating system